Cybersecurity and cyber defence in the emerging democracies. Issue 3 (1st September 2020) - Solar, Carlos
ABSTRACT: How do we interpret current cybersecurity and cyber defence affairs beyond what we know from the advanced democracies and industrialised states? This article argues that in the emerging democracies, the military is on its way to being the dominant force controlling cyber centres or commands emulating those already established in the global North. There are three main takeaways from such developments when using the case study of the western hemisphere. First, states in the region have decided to manage their cyber affairs through inter-governmental and military-to-military diplomacy with more powerful states, such as the United States. Second, governments are eager to set up interactive policy communities at the national level to review cyber risks together with those in the defence sector. Third, militarising cyberspace in fragile political and policy settings can become somewhat risky for democratic governing. Ultimately, marrying the protection of the digital space to highly politicised armed forces might turn into a challenge when trying to set up a secure and egalitarian internet.